2014
DOI: 10.1039/c4ra09129a
|View full text |Cite
|
Sign up to set email alerts
|

Waterproof and breathable membranes of waterborne fluorinated polyurethane modified electrospun polyacrylonitrile fibers

Abstract: Creating an efficient and cost-effective approach that can provide advanced microporous membranes with high waterproofness and good breathability has proved to be tremendously challenging. This work responds to these challenges by designing, fabricating and evaluating an electrospun polyacrylonitrile (PAN) fibrous membrane which was modified with waterborne fluorinated polyurethane (WFPU) to achieve high waterproof and breathable performances. By employing the WFPU modification, the pristine PAN fibrous membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…Figure c presents the O1s spectrum consisting of of three fitted curves with binding energies of 532.3 (CO), 532.9 (CO), and 533.6 eV (SiO). Meanwhile, Si2p curve could be resolved into three component peaks of 102.5 (OSiO), 103.5 (CSi), and 104.2 eV (Si(O) 4 ) , as depicted in Fig. d.…”
Section: Resultsmentioning
confidence: 98%
“…Figure c presents the O1s spectrum consisting of of three fitted curves with binding energies of 532.3 (CO), 532.9 (CO), and 533.6 eV (SiO). Meanwhile, Si2p curve could be resolved into three component peaks of 102.5 (OSiO), 103.5 (CSi), and 104.2 eV (Si(O) 4 ) , as depicted in Fig. d.…”
Section: Resultsmentioning
confidence: 98%
“…Among them, surface modification and thermal post‐treatment have been also proposed to improve waterproof/breathable performance . For instance, Wang et al prepared a waterborne fluorinated polyurethane modified electrospun polyacrylonitrile fibrous membrane, which possessed relatively high tensile strength (14.4 MPa), hydrostatic pressure (83.4 kPa), and WVTR (9.2 kg m −2 d −1 ). Sheng et al found that the thermal treated polyacrylonitrile/fluorinated polyurethane nanofibrous membranes with fiber‐fiber bonding structure exhibited the improved tensile strength (from 3.11 to 9.4 MPa), hydrostatic pressure (from 53 to 114.6 kPa) and WVTR (from 8.7 to 10.1 kg m −2 d −1 ) by adjusting heating temperature and time.…”
Section: Introductionmentioning
confidence: 99%
“…The above‐mentioned doping modifications show limited effect on improving hydrophobicity of extremely hydrophilic nanofibers, such as PAN, polyvinyl alcohol (PVA), and electrospun inorganic nanofibers. In view of this, many researchers have applied surface modification treatment to develop W&B membranes with hydrophobic materials including FPU, fluoroalkylsilane (FAS), polydimethylsiloxane (PDMS), and amino‐silicone oil (ASO) . Combining the virtues of high porosity of nanofibers and hydrophobic property of surface modification layer, this strategy could realize the effective regulation of pore structure and surface wettability of electrospun membranes simultaneously, which is applicable to construct electrospun W&B membranes .…”
Section: Surface Modified Electrospun Wandb Membranesmentioning
confidence: 99%
“…a) Schematic illustration for fabrication of WFPU@PAN fibrous membranes and θ adv of WFPU@PAN‐8 fibrous membranes modified with WFPU emulsions with various concentrations. Reproduced with permission . Copyright 2014, Royal Society of Chemistry.…”
Section: Surface Modified Electrospun Wandb Membranesmentioning
confidence: 99%
See 1 more Smart Citation